Réponses

Meilleure réponse !
2013-09-18T20:25:12+02:00
A)
x²-6x+9=(x-3)²
b)2x-2+(x²-1)=2(x-1)+(x-1)(x+1)=(x-1)(2+x+1)=(x-1)(3+x)
c)5x^4-45²=5x²(x²-9)=5x²(x-9)(x+9)
d) x^5+4x^4+4x^3=x^3(x²+4x+4)=x^3(x+2)²
e)25x²-4+(5x+2)(4x-7)=(5x)²-2²+(5x+2)(4x-7)=(5x-2)(5x+2)+(5x+2)(4x-7)
=(5x+2)(5x-2+4x-7)=(5x+2)(9x-9)
f)(x+1)²+(x-1)²=(x+1)(x+1)+(x-1)(x+1)=(x+1)(x+1+x-1)=(x+1)2x
g) (3x-6)(2x-1)-3(4-x²)=(3x-6)(2x-1)-3(2²-x²)
(3x-6)(2x-1)-3(2-x)(2+x)=(3x-6)(2x-1)+(-6+3x)(2+x)=
=(3x-6)(2x-1)+(3x-6)(2+x)=(3x-6(2x-1+2+x)=(3x-6)(3x+1)